Identification of alpha‐gal sensitivity in patients with a diagnosis of idiopathic anaphylaxis. Issue 5 (27th December 2017) - Carter, M. C.; Ruiz‐Esteves, K. N.; Workman, L.; Lieberman, P.; Platts‐Mills, T. A. E.; Metcalfe, D. D.
Abstract: IgE antibodies (Ab) specific to galactose‐α‐1, 3‐galactose (alpha‐gal) are responsible for a delayed form of anaphylaxis that occurs 3‐6 hours after red meat ingestion. In a unique prospective study of seventy participants referred with a diagnosis of idiopathic anaphylaxis (IA), six (9%) were found to have IgE to alpha‐gal. Upon institution of a diet free of red meat, all patients had no further episodes of anaphylaxis. Two of these individuals had indolent systemic mastocytosis (ISM). Those with ISM had more severe clinical reactions but lower specific IgE to alpha‐gal and higher serum tryptase levels, reflective of the mast cell burden. The identification of alpha‐gal syndrome in patients with IA supports the need for routine screening for this sensitivity as a cause of anaphylaxis, where reactions to alpha‐gal are delayed and thus may be overlooked.